FOREIGN EXPERIENCE OF COMBATING ILLEGAL MIGRATION IN UKRAINE AND THE POSSIBILITY OF ITS USE IN UKRAINE (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that foreign experience is knowledge, skills, practices and achievements obtained in various spheres of activity abroad. The use of foreign experience allows organizations, governments and individuals to adapt advanced foreign technologies, management models, educational methods and practices to domestic realities. It was established in the context of the analysis of the US experience that in Ukraine it is important to consider local conditions and specifics. One of the first steps could be to improve border controls. This may include the introduction ofmodern monitoring technologies at the border to increase the effectiveness of detecting illegal crossings. An important component is economic and social measures, such as the introduction of a system of mandatory verification of the legal status of workers, which can reduce opportunities for illegal work. During the analysis of the experience of Germany and Italy, attention was focused on the need to implement integration programs for migrants, which will include language courses, professional training and assistance in employment. This will contribute to their quick adaptation and reduction of social tension. The use of modern technologies in the course of border control, such as biometric data and video surveillance systems, will allow more effective monitoring and control of the movement of persons. The creation of migrant reception centers will help provide temporary shelter and assistance, providing adequate living conditions. It was determined during the analysis of the experience of Great Britain that in Ukraine it is also important to expand information resources for potential migrants and ensure their access to comprehensive information about legal migration routes and legal aspects of the migration process.
Keywords: illegal migration; counteraction; foreign experience; administrative and legal regulation; public administration; administrative legislation